Using SINIS and GQM+Strategies to Align Organizational Goals and Service Level Agreement Indicators - Ferreira, Eduardo; Trinkenreich, Bianca; Barcellos, Monalessa Perini; Santos, Gleison (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Context: Lack of alignment between business goals, indicators and IT strategies can directly impact projects and activities prioritizing, decision making and results. Motivation: Aligning ongoing IT projects to strategies and business goals, as well as monitoring deliverables' results and Service Level Agreements (SLA) defined in contracts is a challenging task for IT service organizations. Objective: This paper presents an application of SINIS and GQM + Strategies methods for organizational alignment and definition of goals, strategies and indicators for IT services. Method: We performed a case study in a service management team of a Brazilian large public IT organization. Results: We could properly identify and explain the relation between business goals, indicators, strategies and existing SLA and suggested improvements for SINIS method. Conclusion: SINIS and GQM+Strategies helped organization to provide a clear, explicit and common understanding of IT service goals and how they are related to ongoing strategies, contracts and respective SLA. Besides, SINIS helped the organization on defining a monitoring mechanism for goals achievement by defining proper and relevant indicators, measurement plans and interpretation models for decision making.